THAI TEACHERS CONCEPTIONS OF THE CLT APPROACH IN ENGLISH LANGUAGE EDUCATION - Sureepong Phothongsunan, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The communicative language teaching (CLT) approach and its fundamental principles, including learning to communicate through interaction and engagement, are generally upheld by theories in the area of second language acquisition even though by and large implementing CLT in practice is to some degree difficult and ineffective in many ESL (English as a second language) and EFL (English as a foreign language) contexts. This action research is undertaken to assist a small group of Thai EFL school teachers in developing and implementing context-sensitive CLT through a teacher training program designed for their own professional development as secondary school teachers. Two methods are employed, an observation and a task evaluation. It is found that from the teachers’ practice using CLT in teaching, their classes are hardly communicative in nature as communication is constrained and rather unilateral, mostly directed by the teachers. Some recommendations are made to the teachers under study based on the methods used, addressing fluency rather than accuracy if students’ communicative competence is the goal.